2016
DOI: 10.1039/c5nj02513c
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted green synthesis of some nanoconjugated copolymers: characterisation and fluorescence quenching studies with bovine serum albumin

Abstract: The copolymer POPD-co-PNA quenches BSA fluorescence revealing many of its photophysical characteristics including a higher association constant and its scintillating presence on the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…35,36 Copolymerization of the two monomers was carried out with a view to tailor the opto-electronic and electrochemical properties of copolymers by varying the comonomer ratio. [37][38][39] The copolymers were analysed for their spectral and morphological characteristics by employing infrared (IR), 1 H-NMR, ultraviolet-visible (UV-Vis) spectroscopies, X-ray diffraction (XRD) and transmission electron microscopic (TEM) techniques. Fluorescence spectroscopy and confocal imaging were also carried out to explore the emission characteristics of the copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Copolymerization of the two monomers was carried out with a view to tailor the opto-electronic and electrochemical properties of copolymers by varying the comonomer ratio. [37][38][39] The copolymers were analysed for their spectral and morphological characteristics by employing infrared (IR), 1 H-NMR, ultraviolet-visible (UV-Vis) spectroscopies, X-ray diffraction (XRD) and transmission electron microscopic (TEM) techniques. Fluorescence spectroscopy and confocal imaging were also carried out to explore the emission characteristics of the copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that on incorporation of metallic nanoparticles, interfacial and coordinate interaction between the conjugated chain of PNA and silver is expected to modify the polymer chain reorganization. According to earlier reports, peaks around 2θ =5.8°,9.1°,14.5°, 17.1°, and 23.5° can be correlated to the (020), (010), (200), (100), and (011) planes of the pseudo‐orthorhombic lattice of PNA . Therefore, the low angle peaks present in the PNA‐Ag nanocomposites are attributed to the formation of crystalline PNA micro domains as proposed by Riaz et al …”
Section: Resultsmentioning
confidence: 64%
“…However, in XRD spectra of PNA‐Ag nanocomposites, a difference in number, position, and intensity of peaks was observed. Presence of additional reflections in the 2θ region 6–25° on the XRD spectra of PNA‐Ag nanocomposites indicates that crystallinity and orientation of PNA chains are affected by AgNPs incorporation . Here pristine PNA is prepared by polymerization of NA using APS alone, while during the nanocomposite preparation polymerization is done in the presence of mixed oxidants say AgNO 3 and APS, which may influence the crystallinity, orientation, and chain length of PNA and hence it will be reflected in their XRD patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The fluorescence emission spectrum of pristine PVDF/fun‐PMMA blends and their nanocomposites in DMF were recorded upon excitation of the solutions at λ exc = 380 nm, depicted in Figure . The emission spectra of pristine PVDF/fun‐PMMA shown three different patterns of emission under excitation wavelength at relatively very high intensity, showed that the number of decaying excited state polymer molecules were at higher value, or, HOMOs and LUMOs were symmetrically disposed . The all samples exhibited an emission peak around 407 nm may be correspond to the PVDF and at around 431 nm may correspond to functionalized‐PMMA revealing a noticeable blueshift with the incorporation of nanosized undoped/doped ZnO; while at low intensity, 457 nm show the functionalized group present in the blended polymers which show noticeable redshift with incorporation of nanoparticles.…”
Section: Resultsmentioning
confidence: 97%